Lower proportion of CD19+IL-10+ and CD19+CD24+CD27+ but not CD1d+CD5+CD19+CD24+CD27+ IL-10+ B cells in children with autoimmune thyroid diseases - Karolina Stożek; Kamil Grubczak; Viviana Marolda; Andrzej Eljaszewicz; Marcin Moniuszko; Artur Bossowski (Taylor & Francis Group, 2020)
Introduction: As it is generally known, regulatory B cells (Bregs) control inflammation and autoimmunity. The significance of Bregs in the population of children with autoimmune thyroid diseases (AITD) still offers plenty of potential to explore. The aim of this study was to estimate the expression of Bregs (phenotype CD19+CD24+CD27+IL-10+, CD19+IL-10+, CD1d+CD5+CD19+IL-10+ and CD1d+CD5+CD19+CD24+CD27+) in a paediatric cohort with AITD and in health controls. Materials and methods: A total of 100 blood samples were obtained from 53 paediatric patients with Graves' disease (GD) (N = 12 newly diagnosed, mean age 12.5 ± 3.5 and N = 17 during methimazole therapy, mean age 12.7 ± 4.4), Hashimoto's thyroiditis (HT) (N = 10 newly diagnosed, mean age 13.3 ± 2.9 and N = 10 during L-thyroxine therapy, mean age 13.7 ± 3.4) and compared with healthy controls (C) (N = 15, mean age 13.1 ± 3.1). The expressions of the immune cell populations were analysed by four-color flow cytometry using a FASC Canto II cytometer (BD Biosciences). Results: There was a decreasing tendency in the number of lymphocytes B producing IL-10 (B10) cells among all B lymphocytes and more widely, also among all lymphocytes, in each study group, as compared to C. We reported a reduction in IL-10 production in Bregs with the expression of CD19+CD24+CD27+IL-10 and CD1d+CD5+CD19+IL-10+ in both untreated and treated AITD. Conclusions: Our data demonstrate that the reduction in the number of Bregs with CD19+CD24+CD27+IL-10+ and CD19+IL-10+ expression could be responsible for breaking immune tolerance and for AITD development in children.